Pengaruh Pengetahuan, Religiusitas dan Lingkungan Keluarga terhadap Minat Berkarir di Bank Syariah Dengan Memoderasi Motivasi - Fariza Islamiyah; Luqman Hakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the careers that can be an option for students of Islamic Economics is a career in Islamic Banking. This study was conducted to analyze the influence of Islamic bank knowledge, religiosity, and family environment on interest in a career in Islamic banks, with motivation as a variable of moderation. The population in this study comprised 164 students of the Islamic Economics Study Program, with a sample of 116 students selected using a simple random sampling method. Data collection was carried out by distributing questionnaires in the form of Google Forms. The data analysis techniques performed in this study included instrument validity and reliability tests, classical assumption tests such as normality tests, multicollinearity tests, and heteroscedasticity tests. Hypothesis testing included multiple linear regression tests and MRA tests. The results of the analysis using the SPSS 26 program showed that knowledge of Islamic banks, religiosity, and family environment significantly influence career interest in Islamic banks. However, the motivation variable could not moderate the influence of Islamic bank knowledge, religiosity, and family environment on career interest in Islamic banks. This indicates that while these factors are important, motivation alone does not strengthen their impact on career interest in this field.